Pengukuran Emisi Gas Buang pada Bus Antar Kota di Terminal Transit Passo Kecamatan Baguala Kota Ambon - Kornelis U. Rumselly; Arfan Ohorella (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background. Public transportation of vehicles coming in and going out from the Passo Transit Terminal, along with its location close to the market, can influence the levels of CO and HC in the exhaust gases from the vehicles. This can affect the air quality around the area. This is because the intercity buses use diesel fuel, some of them are old, and others have been operating for about 10 years with only 4 to 5 months before their last maintenance. Because of this, the researcher wants to study the levels of CO and HC in the exhaust gas emissions from the vehicles. Research Objective. To check the air quality of the exhaust gas emissions from intercity buses at the Passo Transit Terminal. Method. This study is a descriptive research that includes laboratory tests conducted at the HipperKes Laboratory Center. The population of this study includes 20 intercity buses, with a sample of 2 buses selected based on inclusion and exclusion criteria. Results and Discussion. The results of the CO levels show that bus 1 has 1.77% and bus 2 has 0.22%, which exceed the standard quality level of 0.5% as stated in the Regulation of the Minister of Environment and Forestry Number 8 of 2023. Conclusion and Suggestions. The parameters measured do not meet the required exhaust emission quality standards. The community and passengers are encouraged to increase awareness and use personal protective equipment such as masks